Pengaruh Iklan TerhPengaruh Iklan Terhadap Keputusan Pembelian Konsumenadap Keputusan Pembelian Konsumen - Abednego Stephen; Athluna Canthika; Davin Subrata; Devina Veronika (Universitas Prasetiya Mulya, 2019)
Advertisement is one of the most common way to promote and create awareness of a product. However it is still uncertain to measure the effect of advertisement, especially on customer’s buying decision. The objective of this paper is to identify how much advertisement impacts on consumers buying decision. The research uses quantitative analysis by analyzing online survey data gathered from 280 respondent across Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi). Statistical method such as correlation analysis, descriptive statistics, and regression analysis was used and the result from 244 valid respondents showed that the independent variable brand recall and stimulation have an impact on consumers’ buying decision while the other three variables which are necessity, pleasure, and dominance do not have an impact on consumers’ buying decision.